Clinical and functional predictors of unsatisfactory outcomes of x-ray endovascular treatment in patients with diabetic foot syndrome and coronary heart disease - Zufarov M.M.; Kamalov S.T. (International Journal of Medical Science and Public Health Research, 2025)
Purpose. To determine the clinical and functional parameters associated with unsatisfactory outcomes of X-ray endovascular treatment in patients with di-abetic foot syndrome (DFS) against the background of coronary heart disease (CHD). Materials and methods. The retrospective analysis included 58 patients treated according to standard management in 2015-2019. A comparative analysis was carried out between subgroups with satisfactory and unsatisfactory treatment outcomes according to clinical and anamnestic indicators, including age, duration of diabetes, HbA1c level, LV ejection fraction, Fontaine and Wagner stages, as well as the degree of polymorbidity and the nature of the purulent-necrotic pro-cess. Outcomes. Unsatisfactory outcomes were registered in 22 (37.9%) pa-tients. Statistically significant risk factors were: age over 70 years, duration of di-abetes ≥11 years, HbA1c level ≥10%, reduced EF (<50%), stages III-IV accord-ing to Fontaine and IV-V according to Wagner. In these patients, deep and com-bined forms of foot lesions (wet gangrene, phlegmon), polymorbidity (≥2 con-comitant diseases) and late presentation (>30 days from the onset of the process) were more common. Conclusion. The predictors of unsatisfactory outcomes of X-ray endovas-cular treatment in patients with DFS and CHD are pronounced disorders of car-bohydrate metabolism, cardiac dysfunction, progressive limb ischemia, deep forms of lesion, and polymorbidity. These data substantiate the need for prelimi-nary risk stratification and comprehensive assessment of the cardiac and vascular status before the intervention.